Sponge city in existing housing stock – more of a dream or reality? - Haase, Dagmar (Frontiers in Environmental Science, 2025)
This paper explores the concept of the ‘sponge city’ and its importance in adapting to climate change. It asks whether it is feasible and effective to retrofit existing urban neighbourhoods with sponge city elements. Furthermore, it explores the extent to which potential sponge city elements could be introduced into different neighbourhoods and their potential impact on local microclimate and water storage. Data collected through fieldwork in two districts in the city of Leipzig, Germany—one old and built-up, and the other prefabricated—provide an excellent overview of urban elements that correspond to sponge city properties. The prefabricated district of Paunsdorf has significantly more and larger flat roof systems, green spaces, urban trees, and in-situ gravel drainage beds. In contrast, the Southern Suburb has more paved road surfaces, period-style buildings with pitched roofs and smaller green spaces. The study shows that, given these features, prefabricated housing estates have greater potential for water-sensitive design. Runoff volume can be reduced by 90% with intensive green roofs, most important given their large proportion of the urban area. In both study areas, changing the surface finish of parking areas was found to significantly increase infiltration when changing recent asphalt or composite pavers. Unsealing using grass pavers would reduce runoff, increase infiltration, and have a significant positive impact on urban heat and stormwater events.